Pelatihan Penerapan, Konfigurasi, Troubleshooting Jaringan Kabel UTP untuk Siswa SMK Pembangunan Mranggen, Jurusan TKJ - Surono Surono; Mohammad Burhan Hanif; Galih Setiarso; Joko Suntoro (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
The rapid development of information technology requires students majoring in Computer and Network Engineering (TKJ) to possess competencies in installing, configuring, and troubleshooting UTP cable networks according to industry standards. This Community Service (PKM) activity is a follow-up to previous training at SMK Pembangunan Mranggen, which had not yet covered advanced practical sessions due to time and facility constraints. Utilizing project-based learning and teaching factory approaches, this training focuses on the hands-on practice of UTP cabling, IP address configuration in real network scenarios, and troubleshooting common network failures. This program aims to directly enhance students' technical skills, thereby supporting their readiness for the Vocational Competency Exam (UKK), Field Work Practices (PKL), and workplace demands as network technicians and IT support.